2017
DOI: 10.1038/srep40993
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Oxidative Stress Triggers Tgf-Beta-Dependent Muscle Dysfunction by Accelerating Ascorbic Acid Turnover

Abstract: Endoplasmic reticulum (ER) and oxidative stress are two related phenomena that have important metabolic consequences. As many skeletal muscle diseases are triggered by oxidative stress, we explored the chain of events linking a hyperoxidized ER (which causes ER and oxidative stress) with skeletal muscle dysfunction. An unbiased exon expression array showed that the combined genetic modulation of the two master ER redox proteins, selenoprotein N (SEPN1) and endoplasmic oxidoreductin 1 (ERO1), led to an SEPN1-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 45 publications
3
23
1
Order By: Relevance
“…Although we and others have shown that the leg muscles of SELENON KO mice show no gross alterations in muscle histology, physiology or in the levels of the ER stress response markers [29] , [36] , [27] , [35] , we had detected a significant increase in the time constant of leg muscle relaxation after a series of tetanic stimuli, which represent an exercise mimetic that challenges SERCA activity [42] and requires an active SERCA [43] . Such a prolonged relaxation time was completely rescued in DKO mice, despite no changes in the resistance to fatigue ( Fig.…”
Section: Resultscontrasting
confidence: 58%
See 4 more Smart Citations
“…Although we and others have shown that the leg muscles of SELENON KO mice show no gross alterations in muscle histology, physiology or in the levels of the ER stress response markers [29] , [36] , [27] , [35] , we had detected a significant increase in the time constant of leg muscle relaxation after a series of tetanic stimuli, which represent an exercise mimetic that challenges SERCA activity [42] and requires an active SERCA [43] . Such a prolonged relaxation time was completely rescued in DKO mice, despite no changes in the resistance to fatigue ( Fig.…”
Section: Resultscontrasting
confidence: 58%
“…Functional interactions between SELENON and ERO1 have been suggested by inducing a myopathic phenotype through the delivery of an ERO1-containing adeno-associated virus to otherwise normal SELENON KO limb muscles. Furthermore, the increased cell survival observed after treating SELENON KO cells with an ERO1 inhibitor is consistent with a role of SELENON in counteracting the effects of ERO1 [27] , [35] .…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations